USE OF RAMAN SPECTROSCOPY IN ENVIRONMENTAL PROTECTION AND MEDICAL ANALYSES - Shahzoda Tillaxujayeva; Sherzodjon Ahmedov (Bright Mind Publishing, 2025)
Raman spectroscopy is a very powerful tool for material analysis, allowing the study of various material properties. Since its discovery, Raman spectroscopy has been used to investigate a range of material characteristics, such as carbon and inorganic properties, providing valuable information about their phases, functions, and defects. Moreover, techniques like surface-enhanced Raman spectroscopy have expanded the application of Raman analysis to biological and analytical fields. Furthermore, the durability and versatility of Raman equipment present a promising solution for conducting field analysis to study a wide range of materials.
Keywords: Raman spectroscopy, qualitative analysis, material characterization, pharmaceutical analysis, soil and water analysis.